2017
DOI: 10.1186/s12913-017-2712-3
|View full text |Cite
|
Sign up to set email alerts
|

Hospital choice in Germany from the patient’s perspective: a cross-sectional study

Abstract: BackgroundIn many countries health policy encourages patients to choose their hospital, preferably by considering information of performance reports. Previous studies on hospital choice mainly have focused on patients undergoing elective surgery. This study examined a representative sample of hospital inpatients across disciplines and treatment interventions in Germany. Its research questions were: How many patients decide where to go for hospital treatment? How much time do patients have before admission? Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 52 publications
1
38
0
12
Order By: Relevance
“…Research showed that a previously made personal experience of patients in a hospital was an influencing factor [5].…”
Section: Heterogeneity Between the Studies Identifiedmentioning
confidence: 99%
See 1 more Smart Citation
“…Research showed that a previously made personal experience of patients in a hospital was an influencing factor [5].…”
Section: Heterogeneity Between the Studies Identifiedmentioning
confidence: 99%
“…Besides surgical reputation and surgical competency, hospital reputation and distance to the hospital are the primarily important attributes by which patients choose their surgeon [4]. In another study, previous personal experiences in the hospital were the most frequently stated criterion, followed by the hospital's reputation, recommendation from one's own outpatient caregivers, distance from home and recommendations from relatives [5].…”
Section: Introductionmentioning
confidence: 99%
“…A nationally representative survey of U.S. adults revealed that 85% of respondents reported that WOM recommendations from family or friends were a very important or at least somewhat important factor when choosing their physician (Hanauer, Zheng, Singer, Gebremariam, & Davis, ). Similar studies have also demonstrated the importance of WOM recommendations when choosing hospitals (De Cruppé & Geraedts, ; Martin, ); primary care physicians (Tu & Lauer, ); surgeons (Yahanda, Lafaro, Spolverato, & Pawlik, ); cancer specialists (Jiang et al, ); and other types of healthcare providers and resources (McCaughey, McGhan, Walsh, Rathert, & Belue, ; Pettigrew & Durrance, ; Shreffler‐Grant, Weinert, Nichols, & Ide, ). Individuals can draw out highly experiential insights from their family, friends and acquaintances around their satisfaction and dissatisfaction on a wide array of points of care, such as cost, clinical competencies, staff members' interpersonal skills, and more (Martin, ).…”
Section: Introductionmentioning
confidence: 84%
“…Dazu gehört sicherlich auch eine entsprechende Information der einweisenden Ärzte, die als persönliche Informationslieferanten Nr. 1 der Patienten fungieren [25,26]. Die oft nicht aktuellen Qualitätsberichte der Krankenhäuser gefüllt mit komplizierten Fakten ohne ausreichende Erläuterungen und Bebilderung, die teilweise auf den klinikeigenen Homepages veröffentlicht werden, zeugen eher davon, dass dieses Instrument von den Krankenhäusern selbst nicht ernst genommen wird.…”
Section: Implikationen Für Praxis Und Wissenschaftunclassified